Analysis of changes and influencing factors of stablization treatment effects and bioavailability after freeze-thaw: a case study of Pb-contaminated soil in a non-ferrous metal factory in Northeast China - Hao, Wangwang; Wang, Dongdong; Yu, Miao; Cai, Yun; Wang, Yu (Frontiers in Microbiology, 2024)
IntroductionSolidification/Stabilization techniques are commonly used for the containment and isolation of Pb-contaminated soil, but they cannot reduce the amount of contaminants. Freeze – thaw after stabilization may affect Pb’s environmental behavior and increase the uncertainty of environmental risk.MethodsIn vitro experiments can simulate the bioavailability of heavy metals to the human body, accurately assessing their environmental health risks. In this study, soil samples from Pbcontaminated site are collected from a non-ferrous metal plant in Northeastern China. Through the results of stabilization and freeze–thaw after stabilization experiments, analyzing the changes of physicochemical property, Pb treatment effects (total concentration, leaching concentration, and occurrence forms) and microbial communities, and studying the influencing factors of Pb’s bioavailability.Result and discussionThe results show that stabilization and freeze – thaw after stabilization directly alter soil physicochemical property, thereby affecting the leaching and occurrence form of Pb and microbial communities, and closely related to changes in bioavailability of Pb. Both stabilization and freeze–thaw treatment reduced the leaching concentration of Pb, decreased the proportion of available Pb (acid-soluble state, oxidation state and reduction state), increased the bioavailability of Pb in the gastric phase, but decreased in the intestinal phase; And the dominant bacterial phylum in the soil changed to Firmicutes, the dominant bacterial genus changed to Bacillus; The analysis of the results shows that the bioavailability of Pb is related to soil pH, cation exchange capacity (CEC), soil organic matter (SOM), soil moisture content (SMC), Pb (leaching, acid soluble state, oxidation state, residual state), types of microorganisms in soil.